The Role of Digital Media as a Means of Public Education for the Bina Marga and Bina Construction Service of Lampung Province in Increasing Community Collaboration through Participation in Infrastructure Development (Bandar Lampung Regional Case Study) - Annisa, Meisya; Wuryanti, Lestari; Nursari, Ayu (Nomico, 2026)
The development of digital technology has changed the way people interact, especially in conveying information about infrastructure projects implemented by the government. The purpose of this research is to analyze the function of digital media as a means of public education from the Bina Marga and Bina Konstruksi Office of Lampung Province in increasing community cooperation through involvement in infrastructure development in the Bandar Lampung region. This research applies a quantitative approach by using the survey method. The data collection technique is carried out by distributing questionnaires to residents of Bandar Lampung City who have access and experience in using the digital platform managed by the Bina Marga and Bina Konstruksi Office of Lampung Province. The data obtained was analyzed using multiple linear regression methods with the help of SPSS software. The results of the study show that digital media has a positive and significant impact on citizen participation. Participation measured by indicators such as planning, implementation, supervision, and evaluation indicates that implementation is the most influential indicator. In addition, digital media also plays an important role in community cooperation, and public participation is proven to be a mediation variable between digital media and community collaboration. This finding shows that the more effectively digital media is used as a public education tool, the higher the level of community involvement and cooperation in infrastructure development. This research is expected to be used as an evaluation material and recommendation for government agencies to maximize the utilization of digital media as a public education tool to increase more active and sustainable community participation in infrastructure development.